2018
DOI: 10.5603/njo.2018.0011
|View full text |Cite
|
Sign up to set email alerts
|

External audit of providers of the Cervical Cancer Prevention Programme in Poland in 2016/2017

Abstract: Introduction. The Cervical Cancer (CC) Prevention Programme includes 3 phases: basic (Pap smear collection), diagnostic (Pap smear evaluation) and in-depth (colposcopy/biopsy in case of abnormal smear test findings). The Programme service providers are subject to an external audit and this publication's objective is to analyse its results from 2016 and the first half of 2017. Materials and methods. The audit of the Programme performance in the period 01.01.2016-30.06.2017 was carried out by external auditors b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This is a negative connotation since the number of lesions requiring further diagnostics detected in cervical cytology correlates strongly with numbers of patients tested in outpatient specialty care (AOS) and the percentage of the national population covered by the screening program. In addition, Turkot et al, in their 2018 audit of cytology laboratories in Poland, found there was a significant increase in Pap testing outside the national healthcare program, that is, in the private healthcare sector [11]. Both our results and those of the authors mentioned above may suggest that Pap smear tests are performed in private healthcare.…”
Section: Discussionsupporting
confidence: 65%
“…This is a negative connotation since the number of lesions requiring further diagnostics detected in cervical cytology correlates strongly with numbers of patients tested in outpatient specialty care (AOS) and the percentage of the national population covered by the screening program. In addition, Turkot et al, in their 2018 audit of cytology laboratories in Poland, found there was a significant increase in Pap testing outside the national healthcare program, that is, in the private healthcare sector [11]. Both our results and those of the authors mentioned above may suggest that Pap smear tests are performed in private healthcare.…”
Section: Discussionsupporting
confidence: 65%
“…Its exact screening coverage remains unknown, but published questionnaire data suggest a significant percentage of involvement. In 2012, the participation of Polish women in screening outside of the program was 1.7 times higher than in the program [4,8], and in the last 3 years, about 70% of women have had a Pap test [9], which clearly suggests the dominating role of the private-based screening. There are various models in Polish private-based screening, from cytology to cotesting; the latter was approved in 2013 [10].…”
Section: Introductionmentioning
confidence: 99%